EFFECTS OF QUATERNARY SEA LEVEL CYCLES ON STRONTIUM IN SEAWATER - RELATIONS TO LIFE HABITAT, OXYGEN ISOTOPE COMPOSITION, AND MINOR ELEMENT CHEMISTRY - Stoll H.M.; Schrag D.P. (My University, 1998)
The effects of Quaternary sea level changes on the Sr budget of the ocean are investigated using coupled numerical models of the seawater Sr and Ca budgets. Glacial/interglacial sea level cycles influence the Sr concentration of seawater directly through the periodic exposure and weathering of aragonite on continental shelves and indirectly by modulating the location and extent of carbonate deposition in the ocean. As sea level recedes, brief pulses of Sr are added to the ocean from recrystallization of shelf aragonite; this flux at its maximum is nearly ten times larger than the combined riverine and hydrothermal influx. The large shelf recrystallization fluxes during glacial maxima produce rapid increases in the Sr/Ca ratio of seawater despite the long residence time of Sr in the ocean. Variations in the ratio of aragonitic vs. calcitic sedimentation also influence on the Sr content of seawater because the Sr partitioning coefficient is higher in aragonite; however, this effect is minor compared to shelf aragonite recrystallization. Based on a variety of sensitivity tests, the amplitude of Sr/Ca variations ranges from 1 to 3 % and is maximized by constant rates of total carbonate deposition, extensive aragonite recrystallization, and carbonate budgets which include dissolution of shelf carbonates. Such variation is sufficient to produce up to 1.5°C errors in paleotemperatures calculated from coral Sr/Ca ratios since the last glacial maximum.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная